(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Smokers have a high morbidity and mortality rate and the causes of excess morbidity and mortality include lung cancer, COPD (Chronic Obstructive Pulmonary Disease) and cor pulmonale. An estimated 100 million people died in the 20th century from tobacco-associated diseases. Smoking also affects the performance and cause physical deterioration of pilots. Objectives: To evaluate the effects of smoking on pilots of Bangladesh Air Force (BAF), Dhaka area. Materials and Methods: This cross sectional study was conducted during the period of January to June 2014 among the available pilots of different age and ranks of 6 flying squadrons of BAF Dhaka area. Data were collected by using a pre-tested semistructured questionnaire distributed among the pilots. Information were also collected from Central Medical Board (CMB), BAF about total number of pilots placed in low medical category and nature of their sickness. Finally chest X-ray and ECG of the pilots were done to find out any respiratory and cardiovascular abnormalities. Data obtained were entered into SPSS version 21.0 for analysis. Results: Total 190 pilots were interviewed and among them, 80(42%) were smokers and 110(58%) were non-smokers. Most of the pilots were within the age group of 26-30 years (30%). Out of 80 smoker, 37(46%) smoked for more than 10 years, rest smoked for 10 years and less. Stress was the most common cause of starting smoking (96.3%). Fifty eight (72.5%) pilots agreed that their stamina and physical efficiency decreased due to smoking, 21 (26.3%) experienced breathlessness at high altitude, 26(32.5%) experienced visual disturbance during night flying. Fifty three (66.3%) pilots complained of occasional episode of palpitation along with increase in pulse rate. Thirty one (39%) experienced occasional headache during high altitude flight, 58(72.5%) had heart burn related to smoking. Thirty eight (47.5%) had occasional bouts of cough with sputum and 40(50%) complained of occasional gum bleeding. These pilots also informed that they reported sick several times for headache, heart burn, cough and URTI (Upper Respiratory Tract Infection) and were unfit for flying duties. During January-June 2014, a total of 10 pilots of BAF Dhaka area were placed in low medical category out of them 6 (60%) pilots had smoking habits and suffered from IHD-4 (Ischemic Heart Disease) and HTN-2 (Hypertension). There was statistically significant association between number of the cigarette smoked, period of smoking and physical deterioration of smoker pilots (P<0.05). Those who smoked more than 10 sticks/day and more than 10 years had moderate to severe physical deterioration. Conclusion: Smoking adversely affects all systems of human body. It impairs altitude tolerance, early induction of hypoxia, impairment of night vision. It affects autonomic systems and thus impairs all compensatory mechanism needed at higher altitudes. Morbidity and mortality related to smoking have linear relation. Pilots must be indoctrinated not to smoke for the sake of their safety flight, own life, their families and the nation. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 22-27